ROS responsive nanoparticles loaded with lipid-specific AIEgen for atherosclerosis-targeted diagnosis and bifunctional therapy. (September 2022) - Xu, Hong; She, Peiyi; Ma, Boxuan; Zhao, Zhiyu; Li, Gaocan; Wang, Yunbing
Abstract: Atherosclerosis, which is triggered by endothelial damage, progressive local inflammation and excessive lipid accumulation, is one of the most common cardiovascular diseases in recent years. Drug delivery systems have shown great potential for the accurate diagnosis and effective treatment of early atherosclerosis, but are accompanied by disadvantages such as poor stability, lack of active targeting and non-specific recognition capabilities, which still need to be further developed. In our work, a multifunctional nanoparticle (LFP/PCDPD) with reactive oxygen species (ROS) responsive drug release, lipid removal, and lipid-specific AIE fluorescence imaging was constructed. Cyclodextrin structure with lipid removal function and PMEMA blocks with ROS-response-mediated hydrophobic to hydrophilic conversion were simultaneously introduced into the structure of LFP/PCDPD to load the anti-inflammatory drug prednisolone (Pred) and lipid-specific AIEgen (LFP). The active targeting function of LFP/PCDPD was conferred by the high affinity of dextran to the vascular adhesion molecule-1 (VCAM-1) and CD44 receptor on the surface of broken endothelial cells. After intravenous injection into ApoE −/− mice, LFP/PCDPD actively enriched in the microenvironment of local ROS overexpression and rich lipids in atherosclerosis. Pred and LFP were released while lipids were removed, thus enabling proactive targeting of atherosclerosis and efficient "two-pronged" treatment.